2016
DOI: 10.1038/bjc.2016.313
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3a and the MAPK p38 are activated by cetuximab to induce cell death and inhibit cell proliferation and their expression predicts cetuximab efficacy in colorectal cancer

Abstract: Background:Cetuximab, a monoclonal antibody against EGFR used for the treatment of colorectal cancer (CRC), is ineffective in many patients. The aim of this study was to identify the signalling pathways activated by cetuximab in CRC cells and define new biomarker of response.Methods:We used in vitro, in vivo models and clinical CRC samples to assess the role of p38 and FOXO3a in cetuximab mechanism of action.Results:We show that cetuximab activates the MAPK p38. Specifically, p38 inhibition reduced cetuximab e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…As a positive control, incubation with cetuximab significantly increased caspase-3 activation in spheroids compared with the other conditions ( p  = 0.05), as already described [32]. …”
Section: Resultssupporting
confidence: 79%
“…As a positive control, incubation with cetuximab significantly increased caspase-3 activation in spheroids compared with the other conditions ( p  = 0.05), as already described [32]. …”
Section: Resultssupporting
confidence: 79%
“…13 Previous researches showed that SLC1A5 was highly expressed in many types of cancer including CRC and played an important role in promoting tumor growth. 20 However, the involvement and molecular mechanisms of SLC1A5 in cetuximab treatment on CRC remain largely unknown. 20 However, the involvement and molecular mechanisms of SLC1A5 in cetuximab treatment on CRC remain largely unknown.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19] So far, supplying glutamine for cellular energy production, macromolecular synthesis, redox homeostasis and mTOR signaling activation is the well-known mechanisms of SLC1A5 for promoting tumor growth. 20 However, the involvement and molecular mechanisms of SLC1A5 in cetuximab treatment on CRC remain largely unknown.…”
mentioning
confidence: 99%
“…Previous studies have evaluated the effects of cetuximab only in KRAS wild-type cell lines [14,15]. The resistance mechanism to cetuximab shown by many tumor types remains unclear, although KRAS mutation, as well as EGFR mutation and HER2 or MET activation, has been implicated [15][16][17][18][19][20][21][22]. HRAS mutation or upregulated expression of microRNA-100 and microRNA-125b have also been shown to be associated with cetuximab resistance [23,24].…”
Section: Discussionmentioning
confidence: 99%